Multimodal Deep Learning for Prognosis Prediction in Renal Cancer - Schulz, Stefan; Woerl, Ann-Christin; Jungmann, Florian; Glasner, Christina; Stenzel, Philipp; Strobl, Stephanie; Fernandez, Aurélie; Wagner, Daniel-Christoph; Haferkamp, Axel; Mildenberger, Peter; Roth, Wilfried; Foersch, Sebastian (Frontiers in Oncology, 2021)
Abstract Background: Clear-cell renal cell carcinoma (ccRCC) is common and associated with substantial mortality. TNM stage and histopathological grading have been the sole determinants of a patient’s prognosis for decades and there are few prognostic biomarkers used in clinical routine. Management of ccRCC involves multiple disciplines such as urology, radiology, oncology, and pathology and each of these specialties generates highly complex medical data. Here, artificial intelligence (AI) could prove extremely powerful to extract meaningful information to benefit patients. Objective: In the study, we developed and evaluated a multimodal deep learning model (MMDLM) for prognosis prediction in ccRCC. Design, setting, and participants: Two mixed cohorts of non-metastatic and metastatic ccRCC patients were used: (1) The Cancer Genome Atlas cohort including 230 patients and (2) the Mainz cohort including 18 patients with ccRCC. For each of these patients, we trained the MMDLM on multiscale histopathological images, CT/MRI scans, and genomic data from whole exome sequencing. Outcome measurements and statistical analysis: Outcome measurements included Harrell’s concordance index (C-index) as well as various performance parameters for predicting the 5-year survival status (5YSS). Different visualization techniques were used to make our model more transparent. Results: The MMDLM showed great performance in predicting the prognosis of ccRCC patients with a mean C-index of 0.7791 and a mean accuracy of 83.43%. Training on a combination of data from different sources yielded significantly better results compared to when only one source was used. Furthermore, the MMDLM’s prediction was an independent prognostic factor outperforming other clinical parameters. Interpretation: Multimodal deep learning can contribute to prognosis prediction in ccRCC and potentially help to improve the clinical management of this disease. Patient summary: An AI-based computer program can analyze various medical data (microscopic images, CT/MRI scans, genomic data) simultaneously and thereby predict the survival time of patients with renal cancer.